2014
DOI: 10.7566/jpsj.83.083706
|View full text |Cite
|
Sign up to set email alerts
|

Specific-Heat Evidence of the First-Order Superconducting Transition in Sr2RuO4

Abstract: We investigate the specific heat of ultra-pure single crystals of Sr 2 RuO 4 , a leading candidate of a spin-triplet superconductor. We for the first time obtained specific-heat evidence of the first-order superconducting transition below 0.8 K, namely divergent-like peaks and clear hysteresis in the specific heat at the upper critical field. The first-order transition occurs for all in-plane field directions. The specific-heat features for the first-order transition are found to be highly sensitive to sample … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 47 publications
(59 reference statements)
9
68
1
Order By: Relevance
“…This would be inconsistent with NMR [20,21,22] and neutron scattering [23] experiments which show no observable change in the spin susceptibility through the superconducting transition for in-plane fields. An explanation for this unusual behaviour, compatible with all experimental results, has not been established so far, and experimentalists have been suggesting that it is due to a new pair breaking mechanism [16,18]. In our recent work we suggest that the mechanism could be related to IOE, which can potentially account for both the anisotropy and the change in the character of the transition, as we sumamrize in the following.…”
Section: Magnetic Field Effectsmentioning
confidence: 67%
See 3 more Smart Citations
“…This would be inconsistent with NMR [20,21,22] and neutron scattering [23] experiments which show no observable change in the spin susceptibility through the superconducting transition for in-plane fields. An explanation for this unusual behaviour, compatible with all experimental results, has not been established so far, and experimentalists have been suggesting that it is due to a new pair breaking mechanism [16,18]. In our recent work we suggest that the mechanism could be related to IOE, which can potentially account for both the anisotropy and the change in the character of the transition, as we sumamrize in the following.…”
Section: Magnetic Field Effectsmentioning
confidence: 67%
“…As can be seen in Fig. 2.1 top, the EMM (blue, full line) describes the angular dependence of the upper critical field very well for angles larger than 2 o , but for angles within 2 o of the plane there are clear deviations from the EMM [16,17,18]. The extra suppression of the SC state in this region indicates that there should be a second mechanism which is most effective for in-plane fields.…”
Section: Magnetic Field Effectsmentioning
confidence: 81%
See 2 more Smart Citations
“…Under an in-plane magnetic field, the possibility of SC double transitions has been reported. [12][13][14][15][16][17] However, recent thermal measurements 18,19 revealing the first-order SC transition without a clear second anomaly have suggested that the previously reported anomalies may have originated from the broadening of the first-order transition or from sample mosaicity. Thus, the existence of double transitions in the in-plane magnetic field is still unclear.…”
Section: Introductionmentioning
confidence: 97%